Estilos de aprendizaje y habilidades sociales en estudiantes de básica superior. - Tizon Dioses, Kevin Arturo; Rodriguez Ramirez, Clara Jamilet (Machala, 2021)
Learning styles and social skills constitute two variables that play a significant role during the educational process of students, since they allow to regulate the ways in which learning is established in addition to regulating the social dynamics that give way to learning. school support networks among peers, teachers and other members of the educational community. Hence, the analysis of the relationship presented between these categories allows us to understand the learning dynamics developed within educational communities and, based on the understanding of these relationships, propose intervention proposals that optimize educational processes within the teaching practice. In this sense, the present research has set the objective of determining the level of relationship between learning styles and social skills in upper elementary students of the Manuel Isaac Encalada Zúñiga High School in 2021, for which in the first instance it was necessary starting from the bibliographic analysis of the main theoretical, scientific and methodological conceptions of these variables in order to understand the generalities of these dimensions. This analysis led to the following study problem: What is the relationship between learning styles and social skills in upper elementary students of the Manuel Isaac Encalada Zúñiga High School in 2021?, Based on this research question A problem was constituted with respect to the statistical relationship that arises between these categories, so for the execution of the study a correlational intervention was carried out that allows to analyze the presumed statistical relationship between these variables, so the focus of the present study charged quantitative characteristics that allowed to measure, analyze and establish criteria from the understanding of the implicit phenomena within the study variables. For the selection of the study population, a stratified random sampling was performed with students from a public educational institution that ranged in age ranges between 11 and 14 years, during the development of the study a total of 145 students of the basic education level participated. measure. Among the main findings identified, it was evidenced that there is a statistically significant relationship between the variables of learning styles and social skills, however, this relationship is presented inversely, that is, there is a perfect negative correlation, so these results allowed to conclude that there is a statistically significant relationship between these variables according to the proposed study hypothesis. In this way, the results achieved during the study allowed to structure a methodological guide for the improvement of learning styles and the strengthening of social skills, so for the structure of this guide it was necessary in the first instance to start from the analysis of the postulates scientific, pedagogical, didactic, recreational and curricular that regulate the Ecuadorian educational system and based on these resources structure a versatile intervention tool that allows the teacher to apply these resources based on the educational needs presented by their students.
Los estilos de aprendizaje y las habilidades sociales constituyen dos variables que desempeñan un rol significativo durante el proceso formativo escolar de los estudiantes, debido que las mismas permiten regular las formas en cómo se establecen los aprendizajes y las dinámicas sociales que dan paso a las redes de apoyo escolar entre pares, docentes y otros miembros de la comunidad educativa. El análisis de la relación presentada entre estas categorías permite comprender las dinámicas de aprendizaje gestadas dentro de las comunidades educativas y en función del entendimiento de estas relaciones plantear propuestas de intervención que optimicen los procesos educativos dentro de la praxis docente. En ese sentido, la presente investigación ha planteado como objetivo determinar el nivel de relación entre los estilos de aprendizaje y habilidades sociales en estudiantes de básica superior del Colegio de Bachillerato Manuel Isaac Encalada Zúñiga en el año 2021, para lo cual en primera instancia fue necesario partir del análisis bibliográfico de las principales concepciones teóricas, científicas y metodológicas de estas variables a fin de comprender las generalidades de estas dimensiones. Este estudio conllevo a plantearse el siguiente problema ¿Cuál es la relación entre los estilos de aprendizaje y habilidades sociales en estudiantes de básica superior del Colegio de Bachillerato Manuel Isaac Encalada Zúñiga en el año 2021?, a partir de esta pregunta de investigación se constituyó un problema respecto a la relación estadística que surge entre estas categorías, por lo que para la ejecución se realizó una intervención de tipo correlacional que permita analizar la presunta relación estadística entre estas variables, el enfoque del presente estudio cobro características cuantitativas que permitieron medir, analizar y establecer criterios a partir del entendimiento de los fenómenos implícitos. Para la selección de la población de estudio se realizó un muestreo aleatorio estratificado con estudiantes de una institución educativa publica que oscilaban rangos de edad entre los 11 y 14 años, durante el desarrollo del estudio participaron un total de 145 estudiantes del nivel de educación de básica superior. Entre los principales hallazgos identificados se evidencio que existe una relación estadísticamente significativa entre las variables estilos de aprendizaje y habilidades sociales, no obstante, esta relación se presenta de forma inversa; es decir, se da una correlación negativa perfecta, por lo que estos resultados permitieron concluir que existe una relación estadísticamente significativa entre estas variables conforme la hipótesis de estudio planteada. De este modo, los resultados alcanzados durante el estudio permitieron estructurar una guía metodológica para el mejoramiento de los estilos de aprendizaje y el fortalecimiento de las habilidades sociales, por lo que para la estructura de esta guía fue necesario en primera instancia partir del análisis de los postulados científicos, pedagógicos, didácticos, lúdicos y curriculares que regulan el sistema educativo ecuatoriano y en función de estos recursos estructurar una herramienta de intervención versátil que permita al docente aplicar estrategias en función de las necesidades educativas que presenten sus estudiantes.
Keywords: ESTILO DE APRENDIZAJE; HABILIDAD SOCIAL; CURRICULAR; SIGNIFICATIVO